Uric Acid Level and Its Association with Carotid Intima-Media Thickness in Patients with Cardiac Syndrome X - AÇIKGÖZ, NUSRET; Acikgoz, Nusret; ÖZDEMİR, RAMAZAN; ERMİŞ, NECİP; Yagmur, Julide; Muezzinoglu, Kubra; Karakus, Yasin; CANSEL, MEHMET; PEKDEMİR, HASAN; ÖZDEMİR, Ramazan (My University, 2012)
Objective: The aim of our study was to evaluate serum uric acid level and its relationship with carotid intima-media thickness (CIMT) in patients with cardiac syndrome X (CSX). Subjects and Methods: A total of 50 patients with CSX (28 females/22 males, 51.0 +/- 10.9 years) and 40 controls (27 females/13 males, 53.0 +/- 10.2 years) were included in the study. All subjects underwent a noninvasive stress test and conventional coronary angiography. Serum uric acid levels were measured and B mode ultrasonography was performed to assess CIMT in all subjects. Results: Serum uric acid levels were higher in patients with CSX than in the control subjects (5.1 +/- 1.8 vs. 3.9 +/- 1.3 mg/dl; p = 0.002). The CIMT was higher in patients with CSX than in the control subjects (0.75 +/- 0.18 vs. 0.63 +/- 0.09 mm; p < 0.001). A significant correlation was found between serum uric acid values and CIMT measurements in patients with CSX (r = 0.666, p < 0.001). Conclusions: Serum uric acid levels were higher in patients with CSX and elevated serum uric acid levels were associated with carotid atherosclerosis, thereby indicating that elevated serum uric acid levels might contribute to the development of subclinical atherosclerosis in CSX patients. Copyright (C) 2011 S. Karger AG, Basel